2012
DOI: 10.1111/j.1399-5618.2012.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Trait impulsivity as an endophenotype for bipolar I disorder

Abstract: Objective Impulsivity, conceptualized as impairment in planning and poor attentional and inhibitory control, is a key feature of bipolar disorder. Familial risk for bipolar disorder is known to affect inhibitory control but its impact on the attentional and planning dimensions of impulsivity is still unclear. Methods We administered the Barratt Impulsiveness Scale, version 11 (BIS-11) to 54 euthymic individuals with DSM–IV bipolar I disorder, 57 of their clinically unaffected siblings, and 49 healthy compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 32 publications
5
52
0
1
Order By: Relevance
“…These inconsistencies in past research (eg, Holmes et al, 2009;Lombardo et al, 2012) might be explained if previous studies had different proportions of patients on and off AP medications, or were limited in testing these effects because of small sample sizes.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…These inconsistencies in past research (eg, Holmes et al, 2009;Lombardo et al, 2012) might be explained if previous studies had different proportions of patients on and off AP medications, or were limited in testing these effects because of small sample sizes.…”
mentioning
confidence: 77%
“…Although risky-impulsive behavior is a diagnostic criterion for mania (American Psychiatric Association, 2000) and bipolar patients consistently show abnormalities on selfreport measures of impulsivity, they do not consistently show deficits on behavioral tasks that require planning and forethought (Holmes et al, 2009;Lombardo et al, 2012). These differences may reflect the multi-faceted nature of impulsivity (Dalley and Roiser, 2012), or the measurement tools used to assess the construct (Ouzir, 2013).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Response inhibition and executive functioning tasks have been shown in some studies to be impaired in relatives of individuals with BD relative to HCs (Bora et al 2009), although Ethridge et al (2014) found no response inhibition deficit in first-degree relatives. Self-reported impulsivity is also elevated in siblings of BD probands (Lombardo et al 2012). Impulsive aggression has also been named a potential endophenotype for suicidal behavior (Mann et al 2009;McGirr et al 2009), but impulsivity has not been considered an endophenotype for MDD more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies using the Barratt Impulsiveness Scale (BIS) have shown that impulsivity is present not only during affective states but also in the euthymic state [62,63], and that it also occurs in unaffected siblings [64]. Lombardo et al [64] studied impulsivity using the BIS-11 in euthymic bipolar patients, unaffected relatives, and healthy controls. The BIS-11 scores were higher in unaffected relatives during motor and nonplanning tasks than in controls.…”
Section: The Phenome Of Bd From the Ion Channel Perspectivementioning
confidence: 99%